Toleransi Beragama Dan Kerukunan Dalam Perspektif Islam - Adeng Muchtar Ghazali (UIN Sunan Gunung Djati Bandung, 2016)
Basically as religious beings, human want to live for peace. One result of observations on religious studies shows that Islam as a religion uphold peace and harmony in high esteem. Islam offers the concept of tolerance in diversity, that is tasamuh (tolerance), because it teaches Mouslems the tenets of rahmat (love), hikmat (wisdom), maslahat ammat (universal benefit) and adl (Justice). The concept of tolerance in this context is viewed from many aspects—theology, sociology and cultural studies. Human beings should accept the facts of diversity including that of religions with tolerance that is called religious pluralism. In fact, religious dialogue as a part of tolerance attitude could create harmony in community. For example, both Moslems and non Moslems as citizens of Madinah were protected from their enemy by Muhammad Saw as God’s Messenger, so a Madinah Charter was created.